2009
DOI: 10.5194/acp-9-1521-2009
|View full text |Cite
|
Sign up to set email alerts
|

Fossil and non-fossil sources of organic carbon (OC) and elemental carbon (EC) in Göteborg, Sweden

Abstract: Abstract. Particulate matter was collected at an urban site in Göteborg (Sweden) in February/March 2005 and in June/July 2006. Additional samples were collected at a rural site for the winter period. Total carbon (TC) concentrations were 2.1–3.6 μg m−3, 1.8–1.9 μg m−3, and 2.2–3.0 μg m−3 for urban/winter, rural/winter, and urban/summer conditions, respectively. Elemental carbon (EC), organic carbon (OC), water-insoluble OC (WINSOC), and water-soluble OC (WSOC) were analyzed for 14C in order to distinguish foss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
256
5
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(285 citation statements)
references
References 60 publications
22
256
5
2
Order By: Relevance
“…[12] Studies from Los Angeles and Denver in the 1980s and 1990s showed that TC may originate from fossil sources by up to >70% in large U.S. cities. [16,17] Zurich and Gothenburg as European urban sites show smaller fossil contributions of ~50%, [14,15,22] which are only slightly higher than for most of the investigated European rural sites. [22,30,31] During summer, EC is nearly exclusively of fossil origin with soot production from all kinds of diesel engines as the most important source.…”
Section: Fossil-fuel Sourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…[12] Studies from Los Angeles and Denver in the 1980s and 1990s showed that TC may originate from fossil sources by up to >70% in large U.S. cities. [16,17] Zurich and Gothenburg as European urban sites show smaller fossil contributions of ~50%, [14,15,22] which are only slightly higher than for most of the investigated European rural sites. [22,30,31] During summer, EC is nearly exclusively of fossil origin with soot production from all kinds of diesel engines as the most important source.…”
Section: Fossil-fuel Sourcesmentioning
confidence: 99%
“…[6] For the isolation of both fractions for 14 C analysis, however, such corrections cannot be used. [22] Therefore, the two-step oxidation of OC and EC in pure oxygen is the method of choice, as it is much less prone to charring. [20,22] Further reduction of charring for the isolation of EC is achieved by water extraction of the filters prior to the thermal treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations